“Popularizing” Technocratic Decision-Making: The Formulation of the Philippine Negotiating Position in the WTO Agreement on Agriculture - Encarnacion Tadem, Teresa S. (Kasarinlan: Philippine Journal of Third World Studies, 2011)
One argument raised on the economic crisis, which the Philippines has continuously encountered since the 1970s, is the absence of transparency and accountability in the economic decision-making process. Technocrats who were appointed by the executive had a free rein on deciding economic matters and were only accountable to the Philippine president—a situation that led to failed economic policies which were not attuned to the needs of the people. This was challenged by the 1986 People Power Revolution. With the downfall of the Marcos dictatorship, the martial law technocrats saw their end. However, despite the return in the post-martial law years of “liberal democratic” structures for people participation, technocratic decision-making continued, particularly in the advent of neoliberal globalization. This, however, is continually challenged by civil society and social movements. Such a challenge is seen in the formulation of the Philippine negotiating position in the World Trade Organization (WTO), particularly in the Agreement on Agriculture (AoA) whereby technocrats and civil-society actors have to negotiate and come up with mutually acceptable terms. The following factors brought about this engagement: 1) the failure of the neoliberal paradigm which brought about the 1997 Asian financial crisis; 2) the need to involve civil society in crafting economic policies because of massive worldwide demonstrations against the WTO; 3) the state having to contend with domestic pressures brought about by the democratization process; 4) the public demand for transparency and accountability in economic decision-making; and lastly, 5) the existence of “reformist” technocrats who are open to alternative economic paradigms. These paved the way for the institutionalization of civil-society participation in designing the country’s position on the AoA through the Task Force on WTO Agreement on Agriculture (Re)negotiations (TF-WAAR). Corollary to this is the development of civil society’s technical expertise in the negotiation process and the support of coalition blocs on the Philippine position in agriculture in the WTO.
Keywords: technocrats · economic decision-making · globalization · WTO · civil society · neoliberalism · AoA · TF-WAAR